Catch me if I fall! Enacted uncertainty avoidance and the social safety net as country-level moderators in the job insecurity-job attitudes link - Debus, Maike E.; Probst, Tahira M.; König, Cornelius J.; Kleinmann, Martin (Journal of Applied Psychology, 2012)
Job insecurity is related to many detrimental outcomes, with reduced job satisfaction and affective organizational commitment being the 2 most prominent reactions. Yet, effect sizes vary greatly, suggesting the presence of moderator variables. On the basis of Lazarus's cognitive appraisal theory, we assumed that country-level enacted uncertainty avoidance and a country's social safety net would affect an individual's appraisal of job insecurity. More specifically, we hypothesized that these 2 country-level variables would buffer the negative relationships between job insecurity and the 2 aforementioned job attitudes. Combining 3 different data sources, we tested the hypotheses in a sample of 15,200 employees from 24 countries by applying multilevel modeling. The results confirmed the hypotheses that both enacted uncertainty avoidance and the social safety net act as cross-level buffer variables. Furthermore, our data revealed that the 2 cross-level interactions share variance in explaining the 2 job attitudes. Our study responds to calls to look at stress processes from a multilevel perspective and highlights the potential importance of governmental regulation when it comes to individual stress processes.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Cross-cultural; Enacted uncertainty avoidance; Job insecurity; Social safety net; Stress